ANALISA KEPUASAN PELANGGAN TERHADAP PELAYANAN PERUSAHAAN JASA SEA FREIGHT FORWARDING DI SURABAYA MENGGUNAKAN METODE SERVQUAL - Belva Alisa Ozzura; Devina Puspita Sari; Aditya Maharani (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
Freight forwarding is a service company that aims to represent the interests of the owner of the goods in taking care of all the activities required during delivery to receipt of goods. The subject in this study is a freight forwarding company in Surabaya. The increasing competition among companies engaged in logistics encourages each company to measure the level of customer satisfaction so as to find out how satisfied customers are with the company's services. The research method used is the method of Service Quality (Servqual) and the results in the study obtained all attributes of negative value with the highest value of each dimension is on the Tangibles dimension with attributes of sophistication owned physical facilities and facilities and infrastructure in serving consumers by -0.39, Reliability dimension with attributes of accuracy of handling or administrating records/documents by - 0.74, Responsive dimension with attributes, assurance dimension with employee attributes has a good ability in providing services of -0.67, and Emphaty dimension with employee willingness attributes in informing the existence/constraints of - 0.39. From the analysis it can be concluded that customers are still not satisfied with the company's service so the company must be quick to fix the shortcomings.